ANALISIS DETERMINAN PENGUNGKAPAN RISIKO (STUDI EMPIRIS PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013 – 2015) - Septian Adi Wicaksono; Agustinus Santosa Adiwibowo (Diponegoro Journal of Accounting, 2017)
This research attempted to investigate the influences the number of board of commisioner, the number of board of risk management, profitability, and liquidity. the number of board of commisioner, the number of board of risk management, profitability, and liquidity expected to explain their influences toward the level of corporate risk disclosure.The data used by this research are secondary data taken from Indonesian Site Exchange (IDX) website that is financial companies particulary banking sector listed from 2013-2015. This research uses purposive sampling method, and done data analysis that are descriptive analysis, classical assumption test, and regression test. This research used IBM SPSS 20 to analyzes the data.Based on the results, known that the number of board of commisioner and the number of board of risk management have significantly positive influences toward the level of corporate risk disclosure. While profitability and liquidity has significantly negative influence toward the level of corporate risk disclosure.